Can we predict risk factors for peri-or postoperative complications in asthmatic patients preoperatively? - Kalyoncu, Ali Fuat; Erdogan, Tuba; Goksel, Ozlem; Kirkil, Gamze; Yildiz, Fusun; Gemicioglu, Bilun; Karakaya, Gul (European Respiratory Soc Journals Ltd, 2015)
[Abstract Not Available]
Keywords: Asthma - management